A Murine Model of Mycobacterium kansasii Infection Reproducing Necrotic Lung Pathology Reveals Considerable Heterogeneity in Virulence of Clinical Isolates - Mussi, Vinicius O.; Simão, Thatiana L. B. V.; Almeida, Fabrício M.; Machado, Edson; de Carvalho, Luciana D.; Calixto, Sanderson D.; Sales, Guilherme A. M.; Carvalho, Eulógio C. Q.; Vasconcellos, Sidra E. G.; Catanho, Marcos; Suffys, Philip N.; Lasunskaia, Elena B. (Frontiers in Microbiology, 2021)
Among nontuberculous mycobacteria, Mycobacterium kansasii is one of the most pathogenic, able to cause pulmonary disease indistinguishable from tuberculosis in immunocompetent susceptible adults. The lack of animal models that reproduce human-like lung disease, associated with the necrotic lung pathology, impairs studies of M. kansasii virulence and pathogenicity. In this study, we examined the ability of the C57BL/6 mice, intratracheally infected with highly virulent M. kansasii strains, to produce a chronic infection and necrotic lung pathology. As a first approach, we evaluated ten M. kansasii strains isolated from Brazilian patients with pulmonary disease and the reference strain M. kansasii ATCC 12478 for virulence-associated features in macrophages infected in vitro; five of these strains differing in virulence were selected for in vivo analysis. Highly virulent isolates induced progressive lung disease in mice, forming large encapsulated caseous granulomas in later stages (120-150 d post-infection), while the low-virulent strain was cleared from the lungs by day 40. Two strains demonstrated increased virulence, causing premature death in the infected animals. These data demonstrate that C57BL/6 mice are an excellent candidate to investigate the virulence of M. kansasii isolates. We observed considerable heterogeneity in the virulence profile of these strains, in which the presence of highly virulent strains allowed us to establish a clinically relevant animal model. Comparing public genomic data between Brazilian isolates and isolates from other geographic regions worldwide demonstrated that at least some of the highly pathogenic strains isolated in Brazil display remarkable genomic similarities with the ATCC strain 12478 isolated in the USA 70 years ago (less than 100 SNPs of difference), as well as with some recent European clinical isolates. These data suggest that few pathogenic clones have been widely spread within M. kansasii population around the world.